Thyroglobulin autoantibodies switch to immunoglobulin (Ig)G1 and IgG3 subclasses and preserve their restricted epitope pattern after 131I treatment for Graves' hyperthyroidism: the activity of autoimmune disease influences subclass distribution but not epitope pattern of autoantibodies. (December 2014) - Latrofa, F.; Ricci, D.; Montanelli, L.; Piaggi, P.; Mazzi, B.; Bianchi, F.; Brozzi, F.; Santini, P.; Fiore, E.; Marinò, M.; Tonacchera, M.; Vitti, P.
Summary The subclass distribution of thyroglobulin autoantibodies (TgAb) is debated, whereas their epitope pattern is restricted. Radioidine (131I) treatment for Graves' disease (GD) induces a rise in TgAb levels, but it is unknown whether it modifies subclass distribution and epitope pattern of TgAb as well. We collected sera from GD patients before 131I treatment and 3 and 6 months thereafter. We measured total TgAb, TgAb light chains and TgAb subclasses by enzyme‐linked immunosorbent assay (ELISA) in 25 patients. We characterized the TgAb epitope pattern in 30 patients by inhibiting their binding to 125‐ITg by a pool of four TgAb‐Fab (recognizing Tg epitope regions A, B, C and D) and to Tg in ELISA by each TgAb‐Fab. Total TgAb immunoglobulin (Ig)G rose significantly (P = 0·024). TgAb κ chains did not change (P = 0·052), whereas TgAb λ chains increased significantly (P = 0·001) and persistently. We observed a significant rise in IgG1 and IgG3 levels after 131I (P = 0·008 and P = 0·006, respectively), while IgG2 and IgG4 levels did not change. The rise of IgG1 was persistent, that of IgG3 transient. The levels of inhibition of TgAb binding to Tg by the TgAb‐Fab pool were comparable. A slight, non‐significant reduction of the inhibition by the immune‐dominant TgAb‐Fab A was observed 3 and 6 months after 131I. We conclude that 131I treatment for GD increases the levels of the complement‐activating IgG1 and IgG3 subclasses and does not influence significantly the epitope pattern of TgAb. In autoimmune thyroid disease subclass distribution of autoantibodies is dynamic in spite of a stable epitope pattern.